IMPLEMENTATION OF WEBSITE-BASED MULTICULTURAL ETHNOLITERACY E-MODULE TO OPTIMIZE THE DIGITAL LITERATURE PLATFORM - Wawan Hermawan (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2026)
The advancement of digital technology has created new opportunities for improving literature learning through interactive and accessible digital platforms. However, students' literary literacy and appreciation remain relatively low due to the limited availability of contextual digital learning resources that integrate multicultural values and local wisdom. This community service program aimed to optimize a digital literature platform through the implementation of a website-based multicultural ethnoliteracy e-module for students at SMP Negeri 1 Puri Mojokerto. The program employed a participatory approach consisting of five stages: needs assessment, socialization, training, implementation of the e-module, and mentoring and evaluation. The developed e-module integrated multicultural literary texts, ethnoliteracy content, multimedia resources, interactive quizzes, discussion forums, and reflective activities within a web-based learning environment. The results demonstrated that the implementation of the e-module increased students’ engagement, motivation, digital literacy, and literary appreciation. Students became more active in reading, discussing, and interpreting literary works while developing greater awareness of cultural diversity, tolerance, and local wisdom values. Teachers also improved their competence in utilizing digital technology for literature instruction. Furthermore, the digital literature platform provided a sustainable learning ecosystem that supports independent learning and continuous access to multicultural literary resources. The findings indicate that the integration of website-based learning technology and multicultural ethnoliteracy effectively enhances literary literacy and appreciation while promoting the productive use of digital technology in secondary education.